Kinetics of the pre-treatment of used cooking oil using Novozyme 435 for biodiesel production - Kathleen F. Haigh; Goran Vladisavljevic; Jim Reynolds; Zoltan Nagy; Basu Saha (2014)
The pre-treatment of used cooking oil (UCO) for the preparation of biodiesel has been investigated using Novozyme 435, Candida antarctica Lipase B immobilised on acrylic resin, as the catalyst. The reactions in UCO were carried out using a jacketed batch reactor with a reflux condenser. The liquid chromatography–mass spectrometry (LC–MS) method was developed to monitor the mono-, di- and triglyceride concentrations and it was found that the method was sensitive enough to separate isomers, including diglyceride isomers. It was found that the 1,3 diglyceride isomer reacted more readily than the 1,2 isomer indicating stereoselectivity of the catalyst. This work showed that Novozyme 435 will catalyse the esterification of free fatty acids (FFAs) and the transesterification of mono- and diglycerides typically found in UCO when Novozyme 435 is used to catalyse the pre-treatment of UCO for the formation of biodiesel. A kinetic model was used to investigate the mechanism and indicated that the reaction progressed with the sequential hydrolysis esterification reactions in parallel with transesterification.